The Challenges in restoration of extensor tendons function at the hand: Report of two cases - Leti Acciaro, Andrea; Colzani, Giulia; Starnoni, Marta; Adani, Roberto (Acta Biomedica Atenei Parmensis, 2021)
Introduction: The authors discuss challenges in extensor function restoration at the finger level following distal posterior interosseous or tendon complex injuries, according to the typologies of lesions or the specific patient requirements. Materials: The authors report on two cases describing challenging resolutions. One patient with EDC lag from zone 6B to 8 requiring FCU prolonged with cadaveric grafts. One young patient with distal posterior interosseous lesion requiring selective tendon transfers to EPL and EIP to restore selective and autonomous index extension. Results: In both cases the main goals were obtained, achieving high index of patient satisfaction and excellent outcomes with the restoration of the extension of the fingers. Conclusions: In distal posterior interosseous nerve lesion, high demanding patients may require selective function to restore fine motor skills, such as autonomous index extension. In extensor tendons loss of substance from zone 6 to 8, involving musculotendinous junction proximally and short remnants distally, by-pass tendon transfer prolonged with cadaveric grafts is required. The authors highlight the techniques available as escape plan according to the necessary solutions.